Workplace hostility: defining and measuring the occurrence of hostility in the workplace - Selden, Meridith Pease (Kansas State University, 2006)
The harmful workplace behavior field, although relatively new, is fragmented. Despite a few collaborative efforts (Fox & Spector, 2005; Keashly & Jagatic, 2003; etc.) there is no agreement on the correct terminology to employ. The current paper corrects this by developing a new scale that is a combination of similar, but previously distinct, variables and concepts. This new scale is comprehensive and based off of an intensive review of the literature.
Keywords: workplace; hostility; denigration; exclusion; interference; scale; Psychology, Industrial (0624)